Anomalous nano-barrier effects of ultrathin molybdenum disulfide nanosheets for improving the flame retardance of polymer nanocomposites. Issue 27 (18th June 2015) - Wang, Dong; Song, Lei; Zhou, Keqing; Yu, Xiaojuan; Hu, Yuan; Wang, Jian
Abstract : Polymer/graphene-analogous nanosheet composites have great potential for improving their physical and mechanical properties during the past few years. Abstract : Polymer/graphene-analogous nanosheet composites have great potential for improving their physical and mechanical properties during the past few years. Herein, ultrathin molybdenum disulfide (MoS2 ) nanosheets were simultaneously exfoliated and non-covalently modified by ultrasonication in an aqueous solution of chitosan. The chitosan-modified MoS2 (CS-MoS2 ) nanosheets were then transferred from the aqueous solution to tetrahydrofuran by a simple solvent-exchange method for the fabrication of epoxy (EP) nanocomposites. Transmission electron microscopy and scanning electron microscopy were performed to display the homogeneous dispersion of CS-MoS2 in an EP matrix. On incorporating 2 wt% CS-MoS2 into an EP matrix, EP nanocomposites exhibited reductions of up to 43.3% and 14.6% in peak heat-release rate and total heat release derived from cone calorimeters compared to those of neat EP, respectively. Moreover, toxic volatiles, such as hydrocarbons, aromatic compounds and CO, that escaped from the flaming EP nanocomposites were decreased compared to that of neat EP, demonstrating the higher smoke safety. Combined with the analyses of char residues and thermal stability of EP nanocomposites, the reduced fire hazards of EP nanocomposites could be attributed to the nano-barrier effects of MoS2, which could effectively inhibit the release of combustible gas to support burning and restrain the effusion of volatile toxic substances that cause the majority of deaths in fires.